2016
DOI: 10.1590/1807-2577.02716
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the distribution of stress and deformation in single implant-supported prosthetic units in implants of different diameters

Abstract: ResumoIntrodução: Quando os níveis de tensão e compressão gerados no sistema osso-implante excederem a capacidade óssea ocorre uma fadiga mecânica, resultando em colapso e perda da osseointegração. Objetivo: Analisar o comportamento biomecânico em próteses unitárias implanto-suportadas com implantes de diferentes diâmetros na região posterior de mandíbula. Material e método: Foram criados três modelos de elementos finitos de implantes cone-Morse de mesmo comprimento, variando-se o diâmetro: 3,3 mm, 4,1 mm e 4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(39 reference statements)
0
1
0
1
Order By: Relevance
“…Many research scientists have considered various problems of the connection between the jaw-bone and the implant [1][2][3][4][5][6][7][8][9][10]. For example, [1] demonstrates that under an oblique loading, the bone resorption occurred earlier, and both the volume of the resorbed bone and the implant movement were greater than with axial loading; [2], by using the analysis of the three-dimensional (3D) finite elements method, studies the impact of an implant's type and length as well as bone quality on the implant's stress-strain state; [3] considers the biomechanical analysis by using the finite element method for implants of different lengths in the rear area of the lower jaw, when the load is applied to the prosthesis attached to one implant; [4] studies the impact of the implant type and length on the stress distribution; [5] studies the impact of the prosthesis material on the bone tissue and implant; in [6], the authors have identified that notwithstanding the angle of inclination or the bone type, the values of stresses are greater in the case of combined loadings than with axial loading; [7] gives an analysis of the stress distribution in the implant in the case of immediate and progressive implant loading for bones of different densities; [8] gives various plans of stress-strain distribution between the bone and the implant at fixing the structure in the surface, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Many research scientists have considered various problems of the connection between the jaw-bone and the implant [1][2][3][4][5][6][7][8][9][10]. For example, [1] demonstrates that under an oblique loading, the bone resorption occurred earlier, and both the volume of the resorbed bone and the implant movement were greater than with axial loading; [2], by using the analysis of the three-dimensional (3D) finite elements method, studies the impact of an implant's type and length as well as bone quality on the implant's stress-strain state; [3] considers the biomechanical analysis by using the finite element method for implants of different lengths in the rear area of the lower jaw, when the load is applied to the prosthesis attached to one implant; [4] studies the impact of the implant type and length on the stress distribution; [5] studies the impact of the prosthesis material on the bone tissue and implant; in [6], the authors have identified that notwithstanding the angle of inclination or the bone type, the values of stresses are greater in the case of combined loadings than with axial loading; [7] gives an analysis of the stress distribution in the implant in the case of immediate and progressive implant loading for bones of different densities; [8] gives various plans of stress-strain distribution between the bone and the implant at fixing the structure in the surface, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Os autores concluíram que os implantes de maior diâmetro distribuem de maneira mais efetiva as cargas oclusais ao tecido ósseo e diminuem as tensões principalmente sob cargas oblíquas. Mannarino et al (2016), avaliaram o comportamento biomecânico de próteses implantossuportadas, com implantes de diferentes diâmetros na região posterior da mandíbula. Foram desenvolvidos 3 modelos para simulação computacional, através do método de elementos finitos.…”
Section: Influência Do Diâmetro Do Implanteunclassified